Reward and Work Motivation. A case study in a chosen government agency in Sarawak - Buang, Umar; Rusli, Ahmad; Dayang Kartini, Abang Ibrahim (2011)
The purpose of the study was to identify the influenced of reward factors towards motivation among the supporting staff. The factors contributed in the study are bonus, free medical treatment, compensation and a safety workplace. A survey method was used to gather 108 usable questionnaires from one selected government agency in Sarawak at five main locations which are in Kuching, Sarikei, Sibu, Miri and Bintulu. Outcomes of Pearson correlation analysis showed that there is only one significant relationship of the factors in this study appeared to be strong in safety workplace with the motivation of the supporting staff. It has proved to be a strong relationship between the variables which is at level of –0.70. The independence t-test and one way analysis of variance showed no significant differences between motivation among the supporting staff through the chosen demographic traits which are position, race and the level of education. The finding of this study showed that reward factors (safety workplace) that influence workers towards motivation. In addition, implications of this study is to compensate suitable rewards packages to be place into consideration in order to increase the supporting staff work motivation and the productivity of the organization.